DEVELOPMENT OF SPORTS IN THE REPUBLIC OF UZBEKISTAN - Muratov Muzaffar Shermamatovich; Toshpulatov Latif (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information about the legal framework for the development of sports in the Republic of Uzbekistan and reforms in the field of physical culture and sports in our country.